DEHYDROCYCLIZATION OF NORMAL HEPTANE TO TOLUENE USING BI-METALLIC REFORMING CATALYSTS - A.S. Nasution (Scientific Contributions Oil and Gas, 1984)
Dehydrocyclization of n-heptane and the influence of benzene on this reaction has been carried out with bi-metallic reforming catalyst at the operating temperature : (from 450Â° to 490C), pressure (from 10 to 30 kg/cm), H/lydrocarbon (from 4 to 12 mole/mote) by using a Catatest unit apparatur.